Pemanfaatan Media Digital sebagai Media Edukasi Anti Perundungan di SDN Lontar Baru Kota Serang - Herliani, Nuni; Maulana, Farid Rizqi; Wardana, Deni (Universitas Nusantara PGRI Kediri, 2024)
The phenomenon of bullying has a negative impact, especially on the mental health of victims, which is an act of violence against children, which must be prevented. Prevention efforts can be made by providing anti-bullying education, which in its implementation can be carried out in classroom learning activities. The research conducted focused on the aim of describing the use of digital media in the form of interactive PowerPoint as an anti-bullying education medium in the school environment. The approach in this study was qualitative with the research subjects being grade IV students. The research instruments used in the study were interview guidelines, questionnaires, tests, and documentation. After conducting several stages of research, the results obtained were that digital media in the form of interactive PowerPoint was proven to be used well as an anti-bullying education medium, this statement was supported by data showing that most students were able to understand the learning material well, and students were satisfied with digital media in the form of interactive PowerPoint.